PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN MOTIVASI KERJA SEBAGAI VARIABEL PEMODERASI (Studi Kasus Pada Organisasi Perangkat Daerah (OPD) Di Kota Jayapura) - Iswahyudi Iswahyudi; Bill J. C. Pangayow; Anthonius H.C Wijaya (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
The objectives in this study are: 1). To analyse the effect of budget participation on Managerial Performance on OPD in Jayapura City; and 2). To analyse the effect of budget participation on managerial performance of OPD in Jayapura City with work motivation as a moderating variable The population in this study were all civil servants in the Regional Devices Organizations (OPD) of the Jayapura City government consisting of 33 OPDs. The sample in this study amounted to 99 people. The statistical method used to test Hypotheses is simple regression and multilevel regression analysis with the interaction test approach Moderating Regression Analysis (MRA). Based on the results of the study, the tcount for the variable budget participation is 2.597 with a significance level of 0.012. With a significance level smaller than 0.05, H1 can be supported or in other words, government participation influences managerial performance. This proves that budget participation has a positive influence on managerial performance. The results of the analysis also show that, there is no influence between work motivation variables in moderating budgetaryparticipation with managerial performance as indicated by the value of t count of 0.030 with a significance of 0.976 which is greater than α = 0.05. Thus, the results of this study state that increasing work motivation does not cause an increase in managerial performance that participates in the budget.